Neighborhoods and youth health: Everybody needs good neighbors? - Evelina Björkegren (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
There are large differences in health across neighborhoods in Sweden. To try to answer if there is a causal link between neighborhood conditions in childhood and youth health, I apply two different empirical strategies. First, I use population wide data on families living in different areas in Sweden, and estimate the effects of childhood neighborhood on youth health using data on families that move across the country. Since the choice of moving and where to live is endogenous, I exploit the timing of moves and estimate the effect of siblings' different exposure time to neighborhoods. The second approach utilizes a governmental policy that assigned refugees to their initial neighborhood in Sweden, potentially offering exogenous variation in neighborhoods and allowing me to study the effect of different neighborhoods on youth health. The findings from the two strategies together imply that there are significant neighborhoods effects on youth health, but that the effects are contemporaneous and there is no evidence of exposure time effects.
Keywords: I14; R00; J62; 330; Health; Inequality; Neighborhoods; Childhood